2010
DOI: 10.1371/journal.pone.0009709
|View full text |Cite
|
Sign up to set email alerts
|

Lifting without Seeing: The Role of Vision in Perceiving and Acting upon the Size Weight Illusion

Abstract: BackgroundOur expectations of an object's heaviness not only drive our fingertip forces, but also our perception of heaviness. This effect is highlighted by the classic size-weight illusion (SWI), where different-sized objects of identical mass feel different weights. Here, we examined whether these expectations are sufficient to induce the SWI in a single wooden cube when lifted without visual feedback, by varying the size of the object seen prior to the lift.Methodology/Principal FindingsParticipants, who be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
123
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 20 publications
8
123
2
1
Order By: Relevance
“…Thus, the cortico-spinal consequences of observing an error (even an error made by oneself) could automatically drive the correction of that error for future lifts, contributing to processes underpinning fingertip force adaptation and perhaps motor learning in general. If so, observation of one's own actions may a critical cue for error-based learning, possibly accounting for our recent findings that lifting without visual feedback impairs fingertip force adaptation (Buckingham and Goodale, 2010a;Buckingham et al, 2011). Thus, one role of the sensorimotor system is to gather evidence about the likely requirements of an upcoming motor plan from a variety of sources to drive successful behaviour.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the cortico-spinal consequences of observing an error (even an error made by oneself) could automatically drive the correction of that error for future lifts, contributing to processes underpinning fingertip force adaptation and perhaps motor learning in general. If so, observation of one's own actions may a critical cue for error-based learning, possibly accounting for our recent findings that lifting without visual feedback impairs fingertip force adaptation (Buckingham and Goodale, 2010a;Buckingham et al, 2011). Thus, one role of the sensorimotor system is to gather evidence about the likely requirements of an upcoming motor plan from a variety of sources to drive successful behaviour.…”
Section: Discussionmentioning
confidence: 96%
“…When they are deprived of vision individuals show deficits in their ability to correct their fingertip force errors, continually lifting objects with forces that reflect how heavy the objects look, rather than how heavy the objects actually are (Buckingham and Goodale, 2010a;Buckingham, Ranger, and Goodale, 2011). These findings indicate that individuals receive valuable information describing the direction and magnitude of a lifting error from visual kinematic cues.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, when asked how heavy each dumbbell felt after completing the experiment, participants reported that the small dumbbell felt heavier than the large dumbbell (t(17) = 2.33, p<.05, Figure 2B). Thus, participants expected the dumbbells to weigh different amounts and experienced a SWI as a consequence (e.g., Buckingham & Goodale, 2010a).…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…We have recently provided further indications of how expectations can affect weight perception, by demonstrating that the SWI can even be induced in a single medium-sized cube. In this study, participants were given a short visual preview of a larger or smaller cube, which they expected to eventually lift without visual feedback (Buckingham & Goodale, 2010a). Prior to actually lifting the cube without vision, however, the viewed large or small cube was discreetly replaced with the same lifted cube, unbeknownst to the lifter.…”
mentioning
confidence: 99%
“…In the material-weight illusion, the one of two equally heavy objects that is made from what seems to be a heavier material seems lighter. The dominant theories of the illusions hold that expectations play a major role in the illusions (see, e.g., Buckingham & Goodale, 2010;Buckingham, Ranger, & Goodale, 2011;Ellis & Lederman, 1998). Objects' weights are, to some degree, compared with their expected weights.…”
mentioning
confidence: 99%